The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.autrev.2020.102494
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related differences in systemic sclerosis

Abstract: Systemic sclerosis (SSc) is a complex autoimmune connective tissue disease which is characterised by widespread tissue fibrosis of the skin and internal organs, widespread vasculopathic alterations and immune system abnormalities. The condition is more common in women, but has a more severe expression of disease and higher mortality in men. Although the aetiopathogenesis of SSc is not yet fully understood, there is emerging evidence of important differences between men and women with the disease. This review b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 81 publications
3
44
0
Order By: Relevance
“…The term TGGNB is used to refer to individuals who express their gender in ways that differ from the established cultural norms where gender is defined from sex assigned at birth. The social marginalisation of TGGNB individuals has a significant impact on their health and quality of life [130]. TGGNB people experience significantly high rates of poor physical and mental health [129].…”
Section: Sex and Gender In Researchmentioning
confidence: 99%
“…The term TGGNB is used to refer to individuals who express their gender in ways that differ from the established cultural norms where gender is defined from sex assigned at birth. The social marginalisation of TGGNB individuals has a significant impact on their health and quality of life [130]. TGGNB people experience significantly high rates of poor physical and mental health [129].…”
Section: Sex and Gender In Researchmentioning
confidence: 99%
“…Since anti-Scl-70 (anti-topo I) antibodies are considered to be associated with dcSSc ( 18 ) we also compared the proportion of memory B cell subsets in anti-topo I positive and negative patients, and found that the percentage of ASM B cells was significantly elevated in anti-topo I positive (median: 4.03, IQR: 2.24–4.49) compared to anti-topo I negative (median: 1.11, IQR: 0.82–1.97) SSc patients (p = 0.016) ( Figure 3B ). Male patients with SSc are reported to have a more severe disease ( 19 ), but even when only female patients were included in the analysis, the significant differences in association with dcSSc could still be observed (data not shown).…”
Section: Resultsmentioning
confidence: 96%
“…Finally, 1 study showed male sex to be associated with severity of GI dysfunction ( 22 ). It is also important to note that the prevalence of SSc is 4- to 5-fold higher among female than male population ( 23 ). Age of presentation with SSc-associated pseudo-obstruction was ∼60 years in 2 prior studies ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%